2019
DOI: 10.1155/2019/3862024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diagnostic Potential of Serum Golgi Protein 73 for Hepatic Necroinflammation and Fibrosis in Chronic HCV Infection with Different Stages of Liver Injuries

Abstract: Background and Aim. Serum Golgi protein 73 (GP73) is a promising alternative biomarker of chronic liver diseases, but most data are from patients with HBV infection rather than HCV. Materials and Methods. Two independent cohorts of chronic hepatitis C (CHC) patients from the 5th Medical Centre of the Chinese PLA General Hospital (n=174) and Beijing Youan Hospital (n=120) with different histories of HCV infection were enrolled. The correlations between serum GP73 and other biochemical indices, as well as its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Transient elastography (TE) is the most accurate method with high sensitivity and specificity for advanced fibrosis and is a rapid and noninvasive method widely used in clinical practice 8‐10 . The serum biomarkers chitinase‐3‐like protein 1 (CHI3L1) and Golgi protein 73 (GP73) are good markers of substantial fibrosis and can accurately distinguish among the different stages of liver fibrosis according to the aetiology of viral hepatitis and alcoholic hepatitis 11‐14 . Wang et al showed that CHI3L1 is a useful noninvasive marker for the assessment of liver fibrosis in chronic hepatitis B patients before and during treatment 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Transient elastography (TE) is the most accurate method with high sensitivity and specificity for advanced fibrosis and is a rapid and noninvasive method widely used in clinical practice 8‐10 . The serum biomarkers chitinase‐3‐like protein 1 (CHI3L1) and Golgi protein 73 (GP73) are good markers of substantial fibrosis and can accurately distinguish among the different stages of liver fibrosis according to the aetiology of viral hepatitis and alcoholic hepatitis 11‐14 . Wang et al showed that CHI3L1 is a useful noninvasive marker for the assessment of liver fibrosis in chronic hepatitis B patients before and during treatment 15 .…”
Section: Introductionmentioning
confidence: 99%
“…GP73 is upregulated in many chronic hepatopathies, including chronic viral hepatitis B and C, alcohol-related liver disease, and AIH [ 36 , 37 , 38 , 39 ]. Additionally, GP73 levels were considerably elevated in patients with significant necroinflammation, fibrosis, or cirrhosis [ 36 , 37 , 40 , 41 , 42 ], suggesting that GP73 could be used as a reliable surrogate marker for the detection of advanced fibrosis and cirrhosis but also for the monitoring of patients with liver diseases [ 16 , 37 , 40 , 43 , 44 , 45 ]. Indeed, recent reports have shown that serum GP73 is an accurate biomarker for the detection of significant fibrosis, bearing higher diagnostic accuracy than APRI and FIB-4 scores and that it could be used as a complementary tool to TE [ 20 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This initial concept raised concerns about its specificity in detecting cirrhosis and the early development of HCC. However, subsequent studies by Xiao et al [ 45 ] demonstrated that COMP is slightly expressed in cirrhotic liver and overexpressed in HCC, while recently, Magdaleno et al [ 23 ] showed that COMP contributes to the progression of liver fibrosis by regulating collagen deposition. Interestingly in the latter study, the authors were able to demonstrate how the absence of COMP was associated with decreased hepatic inflammation and fibrosis in two animal models of induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 However, it has also been reported that serum GP73 is of limited value for the evaluation and monitoring of disease progression, including in the identification of liver necroinflammation and fibrosis in patients with chronic hepatitis C virus infection. 27 Therefore, it is uncertain whether the concentration of GP73 is related to the severity of inflammation in NASH or HF.…”
Section: Introductionmentioning
confidence: 99%